Cost-effectiveness of lung MRI in lung cancer screening - Allen, Bradley; Schiebler, Mark L.; Sommer, Gregor; Kauczor, Hans-Ulrich; Biederer, Jürgen; Kruser, Timothy J.; Carr, James C.; Hazen, Gordon (European radiology, 2019)
Recent studies with lung MRI (MRI) have shown high sensitivity (Sn) and specificity (Sp) for lung nodule detection and characterization relative to low-dose CT (LDCT). Using this background data, we sought to compare the potential screening performance of MRI vs. LDCT using a Markov model of lung cancer screening.
Gesehen am 27.10.2020